The Neurodegenerative Characteristics of Alzheimer's Disease and Related Multi-Target Drug Design Studies - Gulcan, Hayrettin Ozan; Orhan, Ilkay Erdogan (Jenny Stanford Publ Pte Ltd, 2019)
[Abstract Not Available]
Keywords: Beta-Amyloid Aggregation; Monoamine Oxidase Inhibitor; Mannich Base Derivatives; Targeting A-Beta; Dual Inhibitors; In-Vitro; Antioxidant Properties; Mao-B; Cholinesterase Inhibition; Association Workgroups